C-15-functionalized eudesmanolides from Mikania campanulata - Krautmann, Marta Irene (2007)
The aerial parts of Mikania campanulata Gardner afforded the nine new eudesmanolides (1S,4S,5S,6S,7S,10R)-1-hydroxy-15-acetoxyeudesm-11(13)-en-6,12- olide (1), (1S,4S,5S,6S,7S,10R)-1,4-dihydroxy-15-acetoxyeudesm-11(13)-en-6,12- olide (2), (1R,4S,5S,6S,7S,10R)-1,4-dihydroxy-15-acetoxyeudesm-11(13)-en-6,12- olide (3), (1R,4S,5S,6S,7S,10R)-1-hydroxy-4,15-diacetoxyeudesm-11(13)-en-6,12- olide (4), (1S,4R,5S,6S,7S,10R)-1,15-diacetoxy-4-hydroxyeudesm-11(13)-en-6,12- olide (5), (1S,5S,6S,7S,10R)-1-hydroxy-15-acetoxyeudesma-4(15),11(13)-dien-6,12- olide (6), (1S,5S,6S,7S,10R)-1,15-dihydroxyeudesma-3,11(13)-dien-6,12-olide (7a), (1S,2R,5S,6S,7S,10R)-1,2,15-trihydroxyeudesma-3,11 (13)-dien-6,12-olide (8a), and (1R,6S,7S,10R)-1,15-dihydroxyeudesma-4,11(13)-dien-6,12-olide (9a), among which the last three were characterized as their corresponding peracetates (7b-9b). The structures of 1-6 and 7b-9b were elucidated using 1D and 2D NMR measurements, while that of major constituent 1 was confirmed by single-crystal X-ray diffraction analysis, and its absolute configuration evidenced from vibrational circular dichroism measurements, which were compared to results obtained from density functional theory calculations. The chemistry of the large genus Mikania is briefly analyzed. © 2007 American Chemical Society and American Society of Pharmacognosy.